A mud design to improve water-based drilling in clay rich formation - Fakhari, Nikoo (Curtin University, 2022)
This research was initiated to design a water based mud that can keep its functionality in deep intervals or shaly formations where conventional additives lose their functionality. In this study a WBM designed using two green surfactants that not only provide good rheology and filtration control under normal drilling conditions, but also prevents shale swelling in complex geological formations.